Understanding Abortion Behavior: Between Social Culture and Human Rights Law - Gunawan Widjaja (Budapest International Research and Critics University, 2022)
This study of health sciences and human rights aims to explore the evidence of scientific studies of abortion behavior, which is an act of social violence and human rights law. The author believes that abortion is closely related to the law and social culture in a place. Therefore, under the phenomenological approach, we attempt to explore as much data as possible to obtain information relevant to answering the understanding of abortion behavior in terms of human rights law and the social-cultural behavior of a society. We found all the data in answering this work question from various publications in the form of scientific evidence that discussed issues of abortion behavior in terms of various legal and legal perspectives. Then we analyzed the data by involving critical data evaluation, coding system, and drawing relevant conclusions to answer questions with high validity and reliability. The data shows that the behavior of abortion in one place is closely related to the local socio-cultural culture and human rights law. We hope this royal finding can add to the body of knowledge on abortion behavior from various perspectives in future studies.